TRADISI PENGUBURAN PRASEJARAH SUKU NGALUM DI KABUPATEN PEGUNUNGAN BINTANG - Maryone, Rini (BALAI ARKEOLOGI PAPUA, 2012)
Burial conducted Ngalum tribe in earlier times, was the body buried in a hollowed out tree, and burial in caves or large gravel pit. archaeological explorations in the Star Mountains District found two caves in Oksibil District are: Cave Mendalbuk in Kampung Kabiding which functioned as a burial cave, and 1 piece of a niche in the alcove Angsamok Serambakon District Villages Wambakon which functioned as a burial niche.